Management by values and social responsibility in chilean state universities - Gaete Quezada, Ricardo (2020)
The objective of this paper is to describe the organizational values of 18 state universities in Chile from the perspective of Management by Values and Social Responsibility of Universities. This study was conducted using a mixed research design based on the analysis of the contents of universities’ strategic plans and webpages. Results show a higher prevalence of pluralism, democracy and equity, whereas socially responsible behavior is characterized by integrity, excellence and freedom. This study concludes that the universities analyzed have an explicit and intelligible corporate identity, even though the latter does not include values and principles of university social responsibility in most cases.